2013
DOI: 10.1183/09031936.00209412
|View full text |Cite
|
Sign up to set email alerts
|

Lipid mediator profiles differ between lung compartments in asthmatic and healthy humans

Abstract: Oxylipins are oxidised fatty acids that can exert lipid mediator functions in inflammation, and several oxylipins derived from arachidonic acid are linked to asthma. This study quantified oxylipin profiles in different regions of the lung to obtain a broad-scale characterisation of the allergic asthmatic inflammation in relation to healthy individuals.Bronchoalveolar lavage fluid (BALF), bronchial wash fluid and endobronchial mucosal biopsies were collected from 16 healthy and 16 mildly allergic asthmatic indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 28 publications
3
25
0
Order By: Relevance
“…LOX products dominated the oxylipin profile, together with CYP metabolites (around 50% of the content for each pathway) in BAL, while LOX metabolites alone were present at the highest relative concentrations in BW (around 75%). Furthermore, BW contained higher levels of oxylipins than BAL, in agreement with Larsson et al [42]. COX products constituted only 5 of 41 oxylipins in the analytical panel and thereby comprised the smallest fraction of the compounds detected.
Fig.
…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…LOX products dominated the oxylipin profile, together with CYP metabolites (around 50% of the content for each pathway) in BAL, while LOX metabolites alone were present at the highest relative concentrations in BW (around 75%). Furthermore, BW contained higher levels of oxylipins than BAL, in agreement with Larsson et al [42]. COX products constituted only 5 of 41 oxylipins in the analytical panel and thereby comprised the smallest fraction of the compounds detected.
Fig.
…”
Section: Resultssupporting
confidence: 90%
“…Analytes that were responsible for the separation in Fig. 8a were mainly 9(10)-EpOME and 12(13)-EpOME (BAL), as well as 13-HODE and 15-HETE (BW); this finding matches the results from previous studies of healthy individuals [42]. The major N -acylethanolamines responsible for the separation were OEA and SEA which were present at higher concentrations in BW than in BAL (Fig.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Asthma is a complex disease characterized by inflammation throughout the respiratory tract from the large airways to the alveoli. Quantification of lipid metabolites in different regions of the lung, of asthmatics and healthy controls, demonstrated that most differences in the formation of 15-LO-1 derived mediators were detected in the proximal airways and not in BALF [35].…”
Section: Discussionmentioning
confidence: 98%